2019
DOI: 10.1016/j.ifacol.2019.11.801
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Moment Matching for the Simulation-Free Reduction of Structural Systems

Abstract: This paper transfers the concept of moment matching to nonlinear structural systems and further provides a simulation-free reduction scheme for such nonlinear second-order models. After first presenting the steady-state interpretation of linear moment matching, we then extend this reduction concept to the nonlinear second-order case based on Astolfi [2010]. Then, similar simplifications as in Cruz Varona et al. [2019] are proposed to achieve a simulation-free nonlinear moment matching algorithm. A discussion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…In many publications, e.g. [27,19,23,3], it has been shown that the reduction of a nonlinear structural system with a pure linear reduction basis V φ = φ 1,eq , . .…”
Section: Augmentation Of the Reduction Basismentioning
confidence: 99%
See 2 more Smart Citations
“…In many publications, e.g. [27,19,23,3], it has been shown that the reduction of a nonlinear structural system with a pure linear reduction basis V φ = φ 1,eq , . .…”
Section: Augmentation Of the Reduction Basismentioning
confidence: 99%
“…The symmetric tensors K (1) ∈ R n×n , K (2) ∈ R n×n×n and K (3) ∈ R n×n×n×n can be obtained from different strategies [11,19]: they can be calculated analytically within the finite element assembly procedure, numerically via finite differences, or identified via e.g. the Implicit Condensation and Expansion (ICE) method [6] or the Enforced Displacement (ED) method [12,17].…”
Section: Polynomial System Representationmentioning
confidence: 99%
See 1 more Smart Citation